Effect of Injectable Platelet-Rich Fibrin on Diced Cartilage's Viability in Rhinoplasty - Gode, Sercan; Ozturk, Arin; Berber, Veysel; Kısmalı, Erkan (Facial Plastic Surgery, 2019)
Diced cartilage is one of the most widely used camouflage technique in rhinoplasty. Its variable resorption rate creates issues in postoperative time period. Platelet-rich fibrin is an autologous concentrated blood derivative containing growth factors that accelerate tissue healing. The authors evaluate the effect of injectable platelet-rich fibrin (I-PRF) on the viability of diced cartilage, which has been used for dorsum camouflage in rhinoplasty. Forty patients were randomly divided into two groups based on dorsal camouflage grafts: diced cartilage with I-PRF (study group) and diced cartilage without I-PRF (control group). Cartilage graft thickness was measured by linear superficial tissue ultrasound at the postoperative first week and the third month in both groups. The mean cartilage graft thickness loss between the first-week and third-month ultrasound measurements was 0.58 ± 0.21 mm in the study group and 0.82 ± 0.35 mm in the control group. There was significant volume loss in the control group. I-PRF was successful in reducing the resorption rate of diced cartilage on nasal dorsum by either increasing the viability or keeping its form. Sticky cartilage is an easily applicable and reliable technique that may be used to camouflage dorsal irregularities in rhinoplasty.
Keywords: cartilage viability; diced cartilage; nasal dorsum camouflage; platelet-rich fibrin; rhinoplasty